2013
DOI: 10.1159/000353802
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Binucleated Cells with Compression in Atypical Squamous Cells of Undetermined Significance

Abstract: <b><i>Objective:</i></b> To increase the accuracy of the diagnosis of atypical squamous cells of undetermined significance (ASC-US), ASC-US were divided into high-risk human papillomavirus (HPV HR+) and non-high-risk HPV (HPV HR-) cases to analyze the significance of binucleated cells with compression. <b><i>Study Design:</i></b> ThinPrep specimens of ASC-US were examined. This study included 21 CIN and HPV HR+ (CIN+), 19 benign and HPV HR- (B-) and 10 benign and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…There have been a few attempts to identify novel cytomorphologic features that can predict HPV infection in samples that were initially diagnosed with NILM or ASCUS based on the diagnostic criteria presented by the Bethesda system . Bollmann et al tested a PCR‐based HPV assay that could detect 16 HPV genotypes and suggested a predictive model combined with 4 cytomorphologic alterations (namely, subtle nuclear changes, disordered keratinization, abortive koilocytes and measles cells, and degenerative changes), which are mainly focused on high‐power fields observed using the ThinPrep‐based preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few attempts to identify novel cytomorphologic features that can predict HPV infection in samples that were initially diagnosed with NILM or ASCUS based on the diagnostic criteria presented by the Bethesda system . Bollmann et al tested a PCR‐based HPV assay that could detect 16 HPV genotypes and suggested a predictive model combined with 4 cytomorphologic alterations (namely, subtle nuclear changes, disordered keratinization, abortive koilocytes and measles cells, and degenerative changes), which are mainly focused on high‐power fields observed using the ThinPrep‐based preparation.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] There have been a few attempts to identify novel cytomorphologic features that can predict HPV infection in samples that were initially diagnosed with NILM or ASCUS based on the diagnostic criteria presented by the Bethesda system. 6,[22][23][24] Bollmann et al 6 4 Accordingly, false-negative results for these 2 HPV types may lead to critical outcomes in patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, Park et al were among the first to describe so‐called LSIL with marked cytological atypia , which appears to be similar to BCD. In 2013, Washiya et al from Japan assessed the significance of binucleated cells with compression and multinucleated squamous epithelial cells in Thinprep LBC samples. Despite taking a slightly different approach from that of Bethesda 2001 and before the publication of the LAST study and the WHO 2014 classification of cervical dysplasia, the Japanese group studying ASCUS cases found a strong association between the presence of binucleated and multinucleated squamous epithelial cells in ThinPrep ® LBC specimens and (1) high‐risk HPV positivity and (2) follow‐up histological diagnosis of CIN 1‐2.…”
Section: Discussionmentioning
confidence: 99%
“…In the study carried out in Brazil and relating to the comparison of classical and secondary cytological criteria relating to hybrid capture for the diagnosis of cervico-vaginal infection by the human papillomavirus, bi or multi nucleation was identified in ( 68 cases) and dyskeratosis (36 cases) with no statically significant difference [73]. By examining the importance of binuclear cells in cervical specimens using the FISH technique; Binucleated cells were identified by the presence of nuclei pressed against each other as positive compression, and their relationship to the relative light units (RLU) of hybrid DNA capture 2 (HC2) was determined; the authors found that binuclear cells (positive compression) were present in 95.2% of cases of intraepithelial neoplasia of the cervix and that their number increased with the grades of intraepithelial neoplasia of the cervix [74]. During cervical cancer screening performed at Kale Hospital in the Pathology Department of the University of Tokyo's Faculty of Medicine in Japan, microscopic images of precancerous lesions were analyzed on a computer at the 'using a digital image analysis program; the number of dyskeratotic cells observed was 813 out of a total of 4049 cells analyzed, i.e.…”
Section: Cytological Alterations Predictive Of Papillomavirus Infectionmentioning
confidence: 99%